Outcome of Cataract Surgery among Eye Camp Patients of Eastern Nepal - Karn , Rajiv Ranjan; Adhikari , Pankaj Ray; Singh , Sanjay Kumar; Roshan , Abhishek; Thakur, Sudhir Kumar (Journal of Nobel Medical College, 2024)
Background: Outreach camp is helpful for reducing the prevalence of blindness due to cataracts and refractive error. The objective was to evaluate the visual outcome of cataract surgery among camp patients operated at a high volume center of Eastern Nepal. Materials and Methods: Descriptive cross sectional study design was used. The comprehensive eye screening program was conducted and those having cataracts were referred to base hospital for cataract surgery, patients were reexamined at the base hospital again and a small incision cataract surgery with posterior chamber intraocular lens was implanted at Biratnagar Eye Hospital, Biratnagar and Sagarmatha Choudhary Eye Hospital, Lahan. The pre-operative vision was taken during screening and post-operative vision was taken after one-month by performing refraction by trained personnel. Data were extracted from the hospital record; analysis was done using SPSS version 17.0. Descriptive analysis by using frequency, parent age and association was done by using Chi square test with a P-value <0.05 considered as significant. Results: A total of 1426 camp patients were operated. Among them 1113 (78%) were visited after one month post operative follow up at the campsite. There were 744 (52%) female and bilateral affected eyes were 735(52%). Pre-operative presenting visual acuity was <3/60 (37%), which was reduced to (0.2%) after one month follows up of cataract surgery. There was a significant association in pre-operative VA with aided one month to follow up VA. Conclusion: The outcome of the cataract surgery of camp patients operated at base hospitals was good in high-volume hospitals. Follow up after one month was good practice to provide services and measure the outcome of cataract surgery.